Differences in Immunogenicity of HLA Antigens and the Impact of Cross-Reactivity on the Humoral Response - Lucas, Donna P. (Transplantation, 2015)
BACKGROUND: Information about differences in immunogenicity of various HLA antigens may help guide donor selection and identify mismatches to avoid for patients likely to need retransplantation. To date, antibody responses to a wide array of individual mismatched antigens have not been evaluated. METHODS: Frequencies of antibodies to mismatched HLA-A, HLA-B, HLA-DR, and HLA-DQ antigens were determined for 703 renal transplant patients who had no detectable donor-specific antibody before transplantation. The impact of cross-reactive group matching and production of antibodies cross-reactive with mismatched antigens were also assessed. Antibodies were identified using multiplexed bead assays. RESULTS: The overall mean frequencies were similar for HLA-A (53.2%), HLA-DR (52.6%), and HLA-DQ (59.0%) antibodies, but significantly lower for HLA-B antibodies (42.4%). However, the response to individual antigens ranged from 15.0% to 76.2%. Antibody frequencies were reduced significantly for 54 of 62 specificities when the patient possessed an antigen cross-reactive with the donor mismatch, but the magnitude of the effect was variable and ranged from 8% to 83%. Moreover, there was directionality in the protective effect of cross-reactive group matching. Overall mean donor-specific antibody frequencies were comparable for men and women except for a significantly higher frequency of antibodies to HLA-DR among men (56.6% vs. 47.8%, P=0.004). Overall mean frequencies in blacks were higher than, or comparable to those of, whites, but differences were not significant. CONCLUSION: There is considerable variability in the immunogenicity of different HLA antigens that is impacted by the presence or absence of cross-reactive antigens in the patient’s phenotype. This information can be used to augment the immunologic evaluation of donor-recipient pairs.